Factors influencing the choice of health care providing facility among workers in a local government secretariat in south western Nigeria (2013)
Background: There is increasing interest in the choice of health care providing facility in Nigeria. Objectives: This study aimed to assess the factors influencing choice and satisfaction with health service providers among local government staff. Methods: A cross sectional survey of all 312 workers in a Local Government Secretariat in South West Nigeria was done. Chi Square and logistic regression analysis was done. Results: The mean age was 38.6 ± 7.5 years, 55% were females and 71.7% had tertiary education. The median monthly family income of the respondents was N 28, 000 (N3,000 – N500,000), with 24.4% earning a monthly income of N21, 000 to N30, 000. Many (72.3%) utilized public health facilities attributing the choice to the low cost of services. Respondents who are satisfied with their usual care providing facilities are 12.2 times more likely to have used public facilities than private facilities (95%, CI 3.431 – 43.114). Respondents who described the quality with ease of getting care/short waiting times as being good are 3.9 times more likely to have private facilities as their chosen health care providing facility (95%, CI 1.755 – 8.742). Cost/payment for service is 2.9 times more likely to predict the use of public health facility as the usual health care provider. Conclusion: Private facilities though costlier do not appear to be providing better services than public facilities. To increase access to health care the cost of services and the waiting time are important factors to address.